The Relationship between Nurses' Knowledge of Patient Identification and the Implementation of Patient Safety Identification in Inpatient Rooms at Ibu Fatmawati Soekarno Regional General Hospital, Surakarta - Putri, Tika Kusuma; Rizky, Wahyu (Asian Journal of Healthcare Analytics, 2024)
Patient identification is a key component of the six patient safety goals and patient safety is a part of hospital accreditation standards. This study aims to examine the relationship between nurses' knowledge of patient identification and the implementation of patient safety protocols in inpatient settings at Ibu Fatmawati Soekarno Regional General Hospital, Surakarta. The research utilizes a quantitative approach with a cross-sectional design. A total of 42 respondents were selected using total sampling, and data were gathered through questionnaires. The data analysis was performed using the Spearman’s Rho test. The findings indicate that 95.2% of nurses had excellent knowledge, while 4.8% had good knowledge. Regarding the implementation of identification practices, 90.5% were rated as excellent and 9.5% as good. The Spearman’s Rho test revealed a correlation coefficient of 0.000 with p<0.05, indicating a strong positive relationship between nurses’ knowledge and identification practices with a correlation degree of 0.689. This study concludes that the nurses at Ibu Fatmawati Soekarno Regional General Hospital demonstrate excellent knowledge and effectively implement patient identification according to established standards.